Kampo Formulae for the Treatment of Neuropathic Pain ∼ Especially the Mechanism of Action of Yokukansan ∼ - Sunagawa, Masataka; Takayama, Yasunori; Kato, Mami; Tanaka, Midori; Fukuoka, Seiya; Okumo, Takayuki; Tsukada, Mana; Yamaguchi, Kojiro (Frontiers in Molecular Neuroscience, 2021)
Kampo medicine has been practiced as traditional medicine (TM) in Japan. Kampo medicine uses Kampo formulae that are composed of multiple crude drugs to make Kampo formulae. In Japan, Kampo formulae are commonly used instead of or combined with Western medicines. If drug therapy that follows the guidelines for neuropathic pain does not work or cannot be taken due to side effects, various Kampo formulae are considered as the next line of treatment. Since Kampo formulae are composed of two or more kinds of natural crude drugs, and their extracts contain many ingredients with pharmacological effects, one Kampo formula usually has multiple effects. Therefore, when selecting a formula, we consider symptoms other than pain. This review outlines the Kampo formulae that are frequently used for pain treatment and their crude drugs and the basic usage of each component. In recent years, Yokukansan (YKS) has become one of the most used Kampo formulae for pain treatment with an increasing body of baseline research available. We outline the known and possible mechanisms by which YKS exerts its pharmacologic benefits as an example of Kampo formulae’s potency and holistic healing properties.